CHARACTERISTICS AND CAUSES OF SOCIOPATHY SUFFERED BY KAZ BREKKER AS SEEN IN SIX CROWS BY LEIGH BARDUGO - Widiastri, Risnada; Saraswati, Sri; Harjani, Emilia Tetty (Conscientia - Journal on Language, Literature, and Culture, 2023)
The research discussed the characteristics and causes of sociopathy suffered by Kaz Brekker as seen in Six Crows by Leigh Bardugo. As the study talked about the mental health issue of the character in the novel, it applied psychoanalysis approach by Mahroof Hussain. The characteristics of sociopathy were analysed using Kathleen Smith’s theory and to identify the causes of sociopathy, Xuanxin Wen’s theory was employed. To collect data, the library research was carried out. The descriptive qualitative method was used to analyse the data. The result of the research indicated that there were four characteristics of sociopathy suffered by Kaz Brekker. Those characteristics were risk-taking, deceitfulness, hostility, and manipulation. The causes of sociopath suffered by Kaz Brekker were getting neglected, experiencing violence, and experiencing trauma in his childhood.